Inositol and In Vitro Fertilization with Embryo Transfer. (28th February 2017) - Simi, G.; Genazzani, A. R.; Obino, M. E. R.; Papini, F.; Pinelli, S.; Cela, V.; Artini, P. G.
Abstract : Recently, studies on inositol supplementation during in vitro fertilization program (IVF) have gained particular importance due to the effect of this molecule on reducing insulin resistance improving ovarian function, oocyte quality, and embryo and pregnancy rates and reducing gonadotropin amount during stimulation. Inositol and its isoforms, especially myoinositol (MYO), are often used as prestimulation therapy in infertile patients undergoing IVF cycle. Inositol supplementation started three months before ovarian stimulation, resulting in significant improvements in hormonal responses, reducing the amount of FSH necessary for optimal follicle development and serum levels of 17beta-estradiol measured the day of hCG injection. As shown by growing number of trials, MYO supplementation improves oocyte quality by reducing the number of degenerated and immature oocytes, in this way increasing the quality of embryos produced. Inositol can also improve the quality of sperm parameters in those patients affected by oligoasthenoteratozoospermia.